Synthesis of a bio-based flame retardant via a facile strategy and its synergistic effect with ammonium polyphosphate on the flame retardancy of polylactic acid - Zhan, Yuanyuan; Wu, Xujuan; Wang, Shasha; Yuan, Bihe; Fang, Quan; Shang, Sheng; Cao, Chengran; Chen, Gongqing (Polymer degradation and stability, 2021)
•A novel bio-based flame retardant was synthesized via a simple ionic reaction.•The synergistic effects of IFR on combustion behaviors of PLA were explored.•APP/ATMP-NA-Fe endowed PLA with excellent flame-retardant performance. The high flammability and severe melt-dripping during the combustion are the most marked fire hazards for polyesters, such as polylactic acid (PLA). In this work, a bio-based flame retardant (ATMP-NA-Fe) was successfully synthesized by a simple aqueous ionic reaction by using amino trimethylene phosphonic acid (ATMP), nicotinamide (NA) and FeCl3•6H2O as raw materials. The ATMP-NA-Fe and ammonium polyphosphate (APP) have good synergistic effects on improving the flame-retardant performance and retarding the combustion melt-dripping of PLA. With a 10 wt% total loading of ATMP-NA-Fe and APP (1:1), the limiting oxygen index value of corresponding PLA composite (PLA3) increases from 20.1% to 32.8%, and it passes UL-94 V-0 rating without melt dripping. The cone calorimetry results show that compared with pure PLA, the peak heat release rate, total heat release and average mass loss rate of PLA3 are reduced by 66.4%, 14.9% and 76.7%, respectively. Via the analysis on the condensed and gas phase products, the flame-retardant mechanism of PLA/APP/ATMP-NA-Fe composites is proposed. This work provides a new approach for improving flame-retardant performance of PLA and promoting the utilization of renewable resource.